Evaluating the Impact of Monetary Policies in Times of Crisis:The Case of the Hashemite Kingdom of Jordan - Al-Zoubi, Waleed; Malahim, Sari; Al-Azzam, Hussam (The Arab Journal of Administration, 2023)
The COVID-19 pandemic presented significant difficulties for central banks as they attempted to implement efficient monetary policies that would guide the Jordanian economy toward recovery from these crises. Consequently, this study focuses on how Jordan’s macroeconomic factors and monetary policy interact. In addition to the effects of monetary policy decisions that were made to control the crisis brought on by the Covid-19 pandemic in Jordan between 2011 and 2021. In order to determine the significance of the consumer price index and real GDP in predicting interest rates, the assessment was carried out using descriptive analysis backed by econometric analysis. Taylor model was used to examine the relationship between the interest rate and macroeconomic variables represented by real GDP and inflation rates over the previous ten years, as it will reflect the pandemic’s state and the effectiveness of the government’s monetary policies in controlling the pandemic situation. The most noteworthy conclusion of the study is that the application of Taylor’s rule through the study of interest rates on credit facilities of licensed banks-loans and advances to represent monetary policy as a dependent variable, GDP at the constant market rate, and inflation as measured by the consumer price index as independent variables-showed that interest rates and GDP and interest rates and inflation had positive statistical relationships at the level of significance of 5%. This is in line with economic theory because it is evident that changes in interest rates are positively impacted by changes in real GDP and inflation.